Naya's tutoring tool - McKay, C. R. (writer of juvenile literature) (Power Coders., 2021)
When Naya is asked to tutor a group of younger students, she struggles to get them to read. Then she finds a program on the computer that will give them any subject at their level, including poetry. However, when Peter in the Coding Club uploads Naya's private poems to the program, Naya is upset. Although the children love the poems and are inspired to write their own, Naya must decide if she wants to admit to being the mystery poet and expose a private part of herself.